Pendampingan Pendaftaran NIB sebagai Faktor Kunci Kesuksesan UMKM di Era Digital di Desa Sait Buttu Saribu Pamatang Sidamanik - ., Fatimah; Wardana, Aji; Yahya, Harun; Lubis, Siti Zahra Khostamarul Aspia; Khairani, Umi; Ritonga, Suhairi; Kataren, Yogi Karmelta (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
Head of BPS Pematangsiantar, Marlise Simamora, through BPS Social Statistics Function Coordinator Eksandi Simanjuntak, explained that the Covid-19 virus pandemic caused the open unemployment rate (TPT) in Pematangsiantar to increase from 11.09 percent in 2019 to 11.50 percent. The aim of this activity is to provide an understanding of the importance of digital NIB and OSS to obtain ease of business legality and other documents such as corporate or individual NPWP. This activity is carried out using the method of socialization and assistance to the community which is carried out for approximately one month and has a special target for people who do not yet have a business registration number (NIB) but already own or run a micro business. This real work lecture activity has been coordinated directly with the Sait Buttu Saribu Saribu Pamatag Sidamanik Village government.